2018
DOI: 10.1080/00016357.2018.1481226
|View full text |Cite
|
Sign up to set email alerts
|

Profile of intrusive luxation and healing complications in deciduous and permanent teeth – a retrospective study

Abstract: Intrusion's profile in DT and PT are different. PT showed more HC than DT, however the level of intrusion and crown direction were not associated with the presence of HC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 23 publications
2
20
0
1
Order By: Relevance
“…In light of these findings, and notwithstanding the limitations of the follow-up period of the study, the authors supported the idea of conservative management of primary tooth intrusion if the permanent tooth germ is not clearly compromised, unless there are issues with patient cooperation. 11 The author's suggestion appears to be consistent with the philosophies underpinning the International Association of Dental Trauma (IADT) guidelines, which advocate extraction of the intruded primary tooth if there is clinical and/or radiographic evidence of displacement into the developing permanent tooth germ. 12…”
Section: Intrusion: Extractionmentioning
confidence: 65%
See 2 more Smart Citations
“…In light of these findings, and notwithstanding the limitations of the follow-up period of the study, the authors supported the idea of conservative management of primary tooth intrusion if the permanent tooth germ is not clearly compromised, unless there are issues with patient cooperation. 11 The author's suggestion appears to be consistent with the philosophies underpinning the International Association of Dental Trauma (IADT) guidelines, which advocate extraction of the intruded primary tooth if there is clinical and/or radiographic evidence of displacement into the developing permanent tooth germ. 12…”
Section: Intrusion: Extractionmentioning
confidence: 65%
“…10 However, a recent retrospective study suggested that conservative measures may be acceptable for primary tooth intrusion. 11 Analysis of dental records showed that the prevalence of primary tooth intrusions in the cohort was 9.98%, and of those injuries, partial intrusion (57.3%) was more common compared to complete intrusion, with palatal orientation of the crown (61.8%) compared to buccal orientation. 11 Of these injuries, the most common management method involved conservative treatment (73.5%) as opposed to extraction.…”
Section: Intrusion: Extractionmentioning
confidence: 91%
See 1 more Smart Citation
“…After removal of duplicates, 1,207 studies remained and were analyzed (reading of titles and abstracts) according to the study criteria. Five studies 5,12,26,27,28 were included for qualitative synthesis, while four 5,12,27,28 were used for the final meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Ese tipo de reabsorción se puede presentar en la superficie externa o interna en el diente siendo contrario a la reabsorción fisiológica. Radiográficamente se observa discontinuidad de la lámina dura, además de la ocurrencia de un padrón acelerado cuando se comparan ambas 4,8,15,16 . Dentro de las lesiones antes destacadas, las fracturas de esmalte y subluxación ocurren con cierta frecuencia en la dentición decidua 8 .…”
unclassified